PENERAPAN METODE EKSPERIMEN BERBANTUAN SOFTWARE PhET PADA MATERI LISTRIK DINAMIS DITINJAU DARI KEMANDIRIAN BELAJAR SISWA KELAS X MAN SINTANG - Saputri, Dwi Fajar; Rahman, Arif Dwi (Jurnal Pendidikan Matematika dan IPA, 2018)
This research aims to investigate the effects of expiremental learning using software PhET for student learning outcomes reviewed by learning independence student. The research is quasy experimental design, with factorial design 2x3. The research samples are the student of XA as the experimental class and the student of XB as the control class. The instruments were test for colecting data of learning outcome and the questionnaire for colecting data of learning indepence student. The result it can be concluded that: 1) There are difference of result of learning outcomes of implementation by experimental learning using software PhET and by conventional learning, the result of learning outcomes of implementation by experimental learning using software PhET better than of result of learning by conventional learning; 2) There are difference of result of learning outcomes in groups of students who have high, medium and low learning independence; 3) There is no interaction beetween learning methods and learning independence on student learning outcomes.Keywords: experimental learning, software PhET, learning outcomes, learning independence.